1998
DOI: 10.1007/s004410050992
|View full text |Cite
|
Sign up to set email alerts
|

The role of voltage-gated Ca 2+ channels in neurite growth of cultured chromaffin cells induced by extremely low frequency (ELF) magnetic field stimulation

Abstract: The ion Ca2+ has been shown to play an important role in a wide variety of cellular functions, one of them being related to cell differentiation in which nerve growth factor (NGF) is involved. Chromaffin cells obtained from adrenals of 2- to 3-day-old rats were cultured for 7 days. During this time, these cells were subjected to the application of either NGF or extremely low frequency magnetic fields (ELF MF). Since this induced cell differentiation toward neuronal-like cells, the mechanism by which this occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
53
1
2

Year Published

1998
1998
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(67 citation statements)
references
References 50 publications
5
53
1
2
Order By: Relevance
“…The lack of significant effect induced by ELF-EMFs, was also supported by the fact that GAP43 and MAP2, neuronal cytoscheletal markers, levels appeared similar in exposed cells to those of control ones. These results are apparently in contrast with the data already published [6,21,24,42] it should be considered that different ELF-EMF intensities and cell models (even if of the same phenotype) were reported.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…The lack of significant effect induced by ELF-EMFs, was also supported by the fact that GAP43 and MAP2, neuronal cytoscheletal markers, levels appeared similar in exposed cells to those of control ones. These results are apparently in contrast with the data already published [6,21,24,42] it should be considered that different ELF-EMF intensities and cell models (even if of the same phenotype) were reported.…”
Section: Discussioncontrasting
confidence: 56%
“…Over the past few years, a lot of data showed that ELF-EMFs exposure can induce modifications of intracellular Ca 2+ levels that can be related to different physiological mechanisms: i.e. differentiation of chromaffin cells into neuronal-like cells [21]; cell death by apoptosis induced by several agents in different human cell systems [66]; and functional modifications of cells of the immune system [67,68]. All of these effects, and many more others, can be attributed to modifications to the Ca 2+ homeostasis by ELF-EMF exposure across different mechanisms, such as the involvement of P2Y membrane receptors [69]; the activation of mechanically operated stretch-activated Ca 2+ channels [70]; and the enhancement of the expression of voltage-gated Ca 2+ channels [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While electromagnetic fields, including pulsed electromagnetic fields (PEMFs), are considered a noninvasive way to promote and align nerve regeneration (Schimmelpfeng et al, 2005), their mode of action at the cellular and molecular levels is unclear. Previous studies indicate that the biological effects of PEMFs, with or without NGF, on neuronal or neuron-like cells appear to be dependent on the usage of a PEMF (Morgado et al, 1998;Schimmelpfeng et al, 2005;Zhang et al, 2006). Few studies have investigated the molecular mechanisms of intracellular signaling in PC12 cells subjected to PEMF stimulation alone.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms whereby ELFMF induces differentiation in chromaffin cells are not clearly understood. However, recent experiments conducted in our laboratory have shown that dehydropyridine-sensitive voltage-gated-L-Calcium channels appear to be involved (Morgado-Valle et al, 1998).…”
Section: Introductionmentioning
confidence: 98%